Copper Metal Removal using Sludge Activated Carbon Derived from Wastewater Treatment Sludge - S. R. M. Kutty, Kutty (2018)

(untitled)
In Malaysia, according to perspective sludge production factor (SPF), wastewater treatment plants produces about 5.3 million m3 of sewage sludge annually, most of this sludge are being wasted (unused) in the landfills. This study employed the use of dry activated sludge as low-cost adsorbent for the removal of copper Cu (II) from wastewater. Adsorption of Cu (II) by sludge activated carbon (SAC) was conducted using batch tests. The effect of contact time and adsorbent dosage on the removal of Cu (II)) from wastewater were investigated. Initial metal concentration was maintained at 100 mg/L. The removal efficiency was found to have relations with the initial Cu (II) concentration, contact time as well as the SAC dosage.